Proceedings of the 14th IEEE/ACM International Conference on Utility and Cloud Computing 2021
DOI: 10.1145/3468737.3494084
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the cost and performance benefits of AWS step functions using a data processing pipeline

Abstract: In traditional cloud computing, dedicated hardware is substituted by dynamically allocated, utility-oriented resources such as virtualized servers. While cloud services are following the pay-as-you-go pricing model, resources are billed based on instance allocation and not on the actual usage, leading the customers to be charged needlessly. In serverless computing, as exemplified by the Functionas-a-Service (FaaS) model where functions are the basic resources, functions are typically not allocated or charged u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…We assumed the SEC network uses AWS pricing [49], which is billed every second. The user cost has three components: (1) cost of using edge servers, (2) cost of transmitting data, and (3) cost of network occupancy.…”
Section: User Costmentioning
confidence: 99%
“…We assumed the SEC network uses AWS pricing [49], which is billed every second. The user cost has three components: (1) cost of using edge servers, (2) cost of transmitting data, and (3) cost of network occupancy.…”
Section: User Costmentioning
confidence: 99%
“…Usually, functions are written in high-level programming languages like Python, Java, or Node.js [25] . NET, and Go [26]. Python is a programming language that is interpreted and has an expressive syntax, which has been likened to executable pseudocode.…”
Section: Lambda Function Implementationmentioning
confidence: 99%
“…A compelling serverless application can be built through using a business logic specified in a workflow to orchestrate functions, and hence workflow scheduling is crucial in serverless computing. Based on the function orchestrator AWS Step Functions (ASF), Mathew et al 24 conducted a series of experiments using a serverless data processing pipeline application based on both ASF Standard and Express workflows. Their results revealed that Express workflows are economical for short‐lived tasks whereas Standard workflows are better suited for long‐running tasks.…”
Section: Background and Related Workmentioning
confidence: 99%